2001
DOI: 10.1007/s003000000197
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diving of harbour seals ( Phoca vitulina ) in Svalbard

Abstract: The distribution, movements and diving of high-arctic harbour seals (Phoca vitulina) were studied in Svalbard, Norway, from 1992 to 1995. A total of 14 seals were equipped with satellite transmitters at Prins Karls Forland (ca. 78°30¢N 12°E). These gave data on position, but ten also gave information on dive depths (N 160,000) and dive durations (N 162,000). Divedepth frequencies show that 50% of the diving is shallower than 40 m, and that 95% of the diving is shallower than 250 m. Based on dive-duration frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…In an attempt to get more information on distribution and movements of the harbour seals in Svalbard, 14 animals were equipped with satellite transmitters during 1992-95 (Gjertz et al 2001 …”
Section: Distribution Abundance and Movementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to get more information on distribution and movements of the harbour seals in Svalbard, 14 animals were equipped with satellite transmitters during 1992-95 (Gjertz et al 2001 …”
Section: Distribution Abundance and Movementsmentioning
confidence: 99%
“…Several studies have been conducted on the harbour seals in Svalbard that shed light on their diving abilities (Gjertz et al 2001, Jørgensen et al 2001. Jørgensen et al (2001) neither development in blood oxygen stores or rates of oxygen consumption is restraining the diving development in these young harbour seal pups.…”
Section: Divingmentioning
confidence: 99%
See 1 more Smart Citation
“…The haul-out behaviour of this population has been studied intensively (Reder et al 2003), and concomittantly with the current stud (see Hamilton et al 2014), but the at-sea behaviour of adult harbor seals re mains largely undocumented. A few animals in this population were tracked through the fall and early winter period via satellite tag deployments in the early 1990s (Gjertz et al 2001) and 3 time-depth recorders (TDRs) were deployed for some weeks in the autumn of 1994 (Krafft et al 2002). However, upto-date distributional information about areas occupied by this population in a broader seasonal perspective is not available.…”
Section: Introductionmentioning
confidence: 99%
“…The west coast of Svalbard is one of the northernmost areas in the Atlantic to be affected by the warm Norwegian Atlantic Current (''the Gulf Stream''); this area does not experience ice-cover outside the inner parts of the fjords during winter. A satellite tracking study of harbour seals on Svalbard showed that adult animals were more or less resident throughout the year in the immediate area of Prins Karls Forland (Gjertz et al 2001). No recent data are available on population size, but surveys during the 1980s concluded that the population consisted of at least 500-600 animals (Prestrud and Gjertz 1990).…”
Section: Introductionmentioning
confidence: 99%